Decoy Receptor 3 Suppresses T-Cell Priming and Promotes Apoptosis of Effector T-Cells in Acute Cell-Mediated Rejection: The Role of Reverse Signaling - Weng, Shuo-Chun; Wen, Mei-Chin; Hsieh, Shie-Liang; Chen, Nien-Jung; Tarng, Der-Cherng (Frontiers in Immunology, 2022)
Background: Decoy receptor 3 (DcR3) belongs to the tumor necrosis factor (TNF) receptor superfamily and neutralizes TNF ligands, including FasL and TRAIL, to prevent T activation during T-cell priming. However, the cellular mechanisms underlying acute cell-mediated rejection (ACMR) remain unknown. Methods: We generated DcR3 transgenic (Tg) mice and mice with high DcR3 expression (HDE) to study both in vivo and in vitro. FasR RNA knockdown in immortalized CD4+CD8+ T-cells was used to survey the role of DcR3 on FasR/ Fas-associated protein with death domain (FADD)/Caspase 8 pathway and its cross-link to TNF receptor-associated factor 1 (TNFR1)-associated death domain protein (TRADD) in suppressing TNFR1. TNF/TRADD knockout mice were used to show the importance of TNF adaptor protein. Results: DcR3.Fc suppressed C57BL/6 female T-cell activation and transformation into CD4+CD69+, CD4+CD44+, and CD4+CD25+Foxp3+ when compared with isotype IgG1 and its co-treatment with FasL/TRAIL after exposing to bone marrow-derived dendritic cells (BMDCs) that carried alloantigen with male H-Y and minor antigenic determinant. Interleukin (IL)-17 and interferon (IFN)-γ productions by BMDC-activated T-cells were lowered after co-treating with DcR3.Fc. DcR3.Fc induced effector T-cells (Teffs), and was susceptible to FasR-mediated apoptosis through the FADD/TRADD/Caspase 8 pathway. After exposing to DcR3.Fc, TRADD was silenced, likely turning down the inflammatory response. Systemic effects of DcR3 Tg mice and HDE phenotype induced by the promoter of cytomegalovirus not only attenuated ACMR severity, but also ameliorated the high serum creatinine and blood urea nitrogen levels even with high T-cell exposure frequencies. Besides, DcR3 has minor biological effects on both MHC-matched and MHC-mismatched models. Conclusions: High DcR3 doses protect renal tubular epithelial cells (RTECs) from acute T-cell attack during the T-cell priming stage via interfering with TNF ligand-mediated reverse signaling, and possibly promoting Teff apoptosis through FasR upregulation. Our findings supported that the decoy receptor is involved in T-cell modulation in kidney transplant rejection.